Total ginsenosides enhance γ-globin expression and fetal hemoglobin production in β-thalassemia models - Cai, Dongling; Chan, Ying; He, Guangyu; Kong, Yamin; Cai, Aiqi; Guo, Yan; Zhu, Baosheng (Frontiers in Pharmacology, 2025)
Introductionβ-thalassemia is a genetic hemoglobinopathy characterized by defective β-globin synthesis and ineffective erythropoiesis. Pharmacological induction of fetal hemoglobin (HbF) via γ-globin gene activation represents a promising therapeutic strategy. Total ginsenosides (TG), the principal active constituents of Panax ginseng, have shown epigenetic and transcriptional modulatory properties, yet their role in HbF induction remains unexplored.MethodsWe evaluated the HbF-inducing potential of TG using human erythroleukemia cell line (K562), primary erythroid precursor cells (ErPCs) derived from CD34+ umbilical cord blood, and Townes transgenic mice. TG was administered at varying concentrations in vitro (25–400 μg/mL) and in vivo (50–800 mg/kg/day for 14 days). HbF and γ-globin expression were quantified by flow cytometry, immunofluorescence, and RT-qPCR. Hemoglobin content, cell viability, and hepatic histology were also assessed.ResultsTG significantly induced HbF production and γ-globin gene expression in both cellular models in a dose-dependent manner. In K562 cells, 200 μg/mL TG elevated γ-globin mRNA by 4.29-fold; in ErPCs, the increase was 1.46-fold. HbF-positive cell populations rose markedly without impairing cell viability or morphology. In vivo, TG treatment at 200 and 400 mg/kg led to 2.8- and 3.1-fold increases in F-cell proportions, respectively, surpassing hydroxyurea controls. No hepatotoxicity was observed upon histopathological examination.DiscussionThese findings establish TG as a potent, well-tolerated inducer of HbF through transcriptional activation of the γ-globin gene. Its efficacy across erythroid cell lines, primary progenitor cells, and transgenic mouse models underscores its translational potential as a natural therapeutic agent for β-thalassemia.